Diaphragmatic hernia: a postnatal complication of anomalous drainage of the umbilical vein. (22nd April 2013) - Jowett, V.; Paramasivam, G.; Seale, A.; Choudhry, M.; Yates, R.; Gardiner, H.
ABSTRACT The ductus venosus (DV) connects the portal venous system to the inferior vena cava. Rarely, the umbilical venous drainage is anomalous, either connecting to the portal sinus within the liver or having an extrahepatic connection, bypassing the liver and draining to one of a variety of sites, including to the heart directly. Prenatally, there is a recognized association of anomalous umbilical venous drainage with aneuploidy and other structural malformations. The fetus may also develop right heart failure because of unregulated volume loading. We report the postnatal development of diaphragmatic hernia in three fetuses with absent DV and umbilical venous drainage to the right atrium directly in two cases and to the coronary sinus in the third. In all fetuses, the abnormality was well‐tolerated in pregnancy, with only a modest degree of right heart dilatation. All three neonates underwent repair of the diaphragmatic hernia and made a good recovery. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.